Penerapan Sistem Pakar Mendiagnosa Kerusakan Sepeda Motor Automatic Dan Injeksi Berbasis Android Dengan Metode Forward Chaining - Sihombing, Darvin Markus; Fahmi, Hasanul (Utility Project Solution, 2021)
Motorbikes are a means of transportation that is widely used by Indonesians, therefore knowledge about motorbikes, especially if there is damage, needs to be controlled by the user. The system that was developed to diagnose motorcycle damage is called an automatic motorcycle failure diagnosis system and injection. The purpose of this research is to develop a diagnosis system for automatic motorcycle damage and injection, which uses the Forward Chaining method where the steps are carried out using basic data and certain rules or codes to build a knowledge base in the form of rules used in diagnosing automatic motorcycle damage and injection. . Method stages starting from assessment, knowledge acquisition, design, testing, documentation and maintenance. Based on the steps that have been carried out, a prototype system for automatic motorcycle damage diagnosis and injection is obtained using the Android Studio programming language. This expert system provides facilities in the form of a page containing the automatic motorcycle damage diagnosis system and injection, then a damage list page, then the user can consult about automatic motorcycle damage and injection according to the symptoms, so the system will display the results of diagnosing automatic motorcycle damage. and injection in the form of the name of the vehicle damage and its solution.